Réponses

2013-07-31T09:51:17+02:00

A  =  x² − 16

    =  x² − 4²

    =  (x + 4) (x − 4)

 

 

B  =  1 − y²

    =  (1 + y) (1 − y)

 

 

C  =  100x² − 9

     = (10x)² − 3²

     =  (10x + 3) (10x − 3)

 

 

D  =  36 − 81z²

    =  6² − (9z)²

    =  (6 + 9z) (6 − 9z)

 

 

E  =  4/π² − 25

    =  (2/π)² − 5²

    =  (2/π + 5) (2/π − 5)

 

F  =  (t + 3)² − 16

    =  (t + 3)² − 4²

    =  (t + 3 + 4) (t + 3 − 4)

    =  (t + 7) (t − 1)

 

 

G  =  (2x + 1)² − 25

     =  (2x + 1)² − 5²

     =  (2x + 1 + 5) (2x + 1 − 5)

     =  (2x + 6) (2x − 4)

 

 

H  =  (3i + 7)² − (i + 5)²

     =  (3i + 7 + i + 5) (3i + 7 − i − 5)

     =  (4i + 12) (2i + 2)